Navigating Menstrual Stigma: Impact of Early Menstrual Conversation on Young Males’ and Females’ Attitudes Towards Menstruation - Pun, Insha; Shearman, Sachiyo M.; Richards, Keith; Muldrow, Adrienne; Powell, Shannon Baker; Pun, Iswar Kumar (Women's Reproductive Health, 2025)
Early conversations about menstruation shape young people's attitudes and behaviors toward it. A mixed-gendered survey of 368 American youths examined the relation between early menstrual conversation (EMC) and their beliefs and attitudes toward menstruation. The current study revealed that males were more likely to endorse menstrual restrictions and secrecy around the topic than were females. Being male, engaging in EMC later in life, discussing a greater number of negative topics, and having fewer opportunities for EMC with peers were found to be associated with restrictive attitudes toward menstruation. The implications of the current study’s findings are discussed. *This is an Accepted Manuscript of an article published by Taylor & Francis in Women's Reproductive Health on 4/30/2025, available at: https://doi.org/10.1080/23293691.2025.2482603.
Keywords: menstruation; Early Menstruation Conversation; stigma; young adults in the United States; gender differences